Assistance In Implementing Madrasah-Based Management At Mts Ummul Quran An-Nurani Tembilahan - Suhana, Suhana; Khairunnisa, Khairunnisa; Sela, Nur; Selfi, Selfi; Nurmadiah, Nurmadiah; Suryani, Suryani; Nurgaya, Siti (Jurnal Masyarakat Mengabdi, 2025)
The purpose of this community service activity is to provide assistance on the implementation of school-based management at MTs Ummul Quran An-Nurani Tembilahan. The method used in this activity is the Participatory Action Learning System (PALS), a method that emphasizes the activeness and participation of partners in the management process of madrasah-based management. The location of this community service activity is in Tembilahan District, Indragiri Hilir Regency, Jalan Perigi Raja. There are 4 stages in the assistance activity, namely: (1) Socialization of madrasah-based management (international language program, Qur'an memorization program, extracurricular). (2) Training (independent curriculum and children's learning methods), assistance in dividing classes according to the child's ability level, holding additional classes. (3) Organizing madrasah-based management so that it can run regularly. (4) Monitoring and evaluation. Through collaboration and hard work, MTs Ummul Qur'an An-Nurani has succeeded in integrating the principles of Islamic education into school management, providing a deep understanding of the vision, mission, and values ​​of the madrasah, and being able to design and implement appropriate strategic steps to strengthen the identity and improve the quality of Islamic education at MTs Ummul Qur'an An-Nurani.